An Effect of Workload and Emotional on Performance on Regional Employees 1 PT Port Indonesia (Persero) - Rudiansyah; Cahyo Pramono; Suwarno (CERED Indonesia Institute, 2022)
This study aims to determine whether partially emotionalpositive and significant effecttoRegional employee performance 1at PT Pelabuhan Indonesia (Persero).What is the workload partiallypositive and significant effecttoperformance on Regional employees1 PT Pelabuhan Indonesia (Persero).Is emotional and workloadtake effecttoemployee performancesimultaneously on Regional 1 PT Pelabuhan Indonesia (Persero).The data analysis technique used is the associative method with the help of the SPSS version 16.0 program. This research uses classical assumption test, multiple linear regression analysis, t test, F test, determination test and path analysis test. The population in this study were all employees of Regional 1 PT Pelabuhan Indonesia (Persero), and a sample of 60 respondents. Primary data collection using a questionnaire. The results showed that partially emotionalpositive and significant effecttoemployee performancein Regional 1 PT Pelabuhan Indonesia (Persero).Partial Workloadpositive and significant effecttoemployee performancein Regional 1 PT Pelabuhan Indonesia (Persero), wheretcount 7.152 > ttable 2.003 and significant 0.000 <0.05. Emotional partiallypositive and significant effecttoemployee performanceat Regional 1 PT Pelabuhan Indonesia (Persero),where tcount 7.464 > ttable 2.003 and significant 0.000 <0.05.